Comparison of leaf epidermis and pollen micromorphology among Dimocarpus longana and Litchi chinensis cultivars in Western Guangdong - LIU Kaidong; YUAN Changchun; CHEN Yan; XIAO Zhengquan; LIU Zhu (浙江大学学报. 农业与生命科学版)
Longan (Dimocarpus longana Lour.) and litchi (Litchi chinensis Sonn.) are famous and special fruits in tropical and subtropical zones. Longan and litchi originate in China, which have been cultivated for more than 2 000 years and both hold abundant germplasm resources. There have been many scientific researches on longan and litchi. However, few systematic studies were conducted on comparison of leaf epidermis and pollen grains between longan and litchi. Therefore, the aim of this study is to compare the differences of leaf epidermis and pollen micromorphology among longan and litchi cultivars, and then to study their phylogenetic relationship.The ultrastructures of leaf epidermis and pollen grains from six longan and six litchi cultivars in Western Guangdong Province were examined using scanning electron microscope, and their relationship with the phylogenetic evolution of the genuses was investigated.The results showed that numerous protuberances could be observed on the lower epidermis. The protuberances of litchi were dome-shaped, and those of longan were long-shaped. There were significant differences in the stomatal densities and sizes of longan and litchi cultivars. The stomatal densities of six longan cultivars were 316.30-406.00 No./mm2, while those of six litchi cultivars were 519.00-655.20 No./mm2. The stomatal lengths of six longan cultivars were 11.16-21.33 μm, while those of six litchi cultivars were 10.38-17.28 μm. The pollen grains of longan and litchi were tricolporate, belonged to N3 P4 C5 type according to Erdtman's NPC system. These pollen grains were sub-spheroidal or wide ellipse in equatorial view, and 3-lobed sub-spheroidal or triangle in polar view. The polar axis lengths of pollen grains in six longan cultivars were 18.31-19.85 μm, while those in six litchi cultivars were 16.19-18.07 μm. The equatorial axis lengths of pollen grains in six longan cultivars was 21.36-24.33 μm, while those in six litchi cultivars were 19.22-21.47 μm. In addition, there were significant differences in some morphological aspects of pollen grains among longan and litchi cultivars, such as pollen size and colporate. The characteristic differences of leaf epidermis and pollen grains were obvious among longan and litchi cultivars.Thus, it is suggested that the micromorphological characters of leaf epidermis and pollen grains are very important for cultivar differentiation in longan and litchi cultivars. Meanwhile, they can also provide valuable information for the study of taxonomy and phylogenesis among D. longana and L. chinensis cultivars.